Juegos serios como método innovador del proceso de aprendizaje de los estudiantes de la carrera Técnico Superior en Enfermería. Instituto San Gabriel 2020. - Huilca Loyola, Angel Polivio (2021)
The present research “Serious games as an innovative method of the learning process of the students of the technical career in nursing. San Gabriel Institute 2020”, it established the purpose of developing a proposal for a teaching method, through the use of serious games to help students of the Technical Nursing career in the learning process. The research had a quantitative approach, with a pre-experimental design, through an application-level bibliographic work. The techniques applied such as the bibliographic analysis, the pre and post test, allowed to determine that this new learning proposal through digital tools using serious games as an innovative tool in the teaching methodology has the sufficient capacity to influence the learning of the students. The population consisted of 196 students. Faced with the problem, a 6-phase methodology was designed and it includes: Serious Game Selection, Teaching Guide, Motivation, Method, Competences and Assessment. It can be concluded that the application of serious games as an innovative method contributes at a level of 40.89% probability in improving the average performance of the teaching-learning process in students of the Technical Career in Nursing of the Instituto Tecnológico San Gabriel.